Meta Analysis Of Learning Models Problem Based Learning In Improving Critical Thinking Skills In Primary Schools - Sururuddin, Muhammad; Suarni, Ni Ketut; Margunayasa, I Gede (IJE : Interdisciplinary Journal of Education, 2024)
This   study   aims   to   analyze   Problem-based   Learning   models intended to improve critical thinking skills in elementary school students. Problem-based learning models are learning processes where students are open minded, reflexive, active, reflective, and critical through real-world context activities. In this study the researchers used a meta-analysis method. First, the researcher formulated the research problem, then proceeded to review the existing relevant research for analysis.  Data were collected by using a non-test technique by browsing electronic journals through Google Scholar and studying documentation in the library. Seven articles were found through Google Scholar and only one was found in the library. Based on the analysis of the results, the problem-based learning model can improve students' thinking ability from as little as 2.87% up to 33.56% with an average of 14.18%.